2019
DOI: 10.24815/siele.v6i1.6659
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of error sources in L2 written English by Indonesian undergraduate students

Abstract: This study investigates second language learners’ production in writing, aiming to understand common problems the learners frequently have with English. The study focuses on the analysis of errors in 100 essays written by 50 Indonesian undergraduate students of English, which is aimed at identifying the commonly occurring errors, classifying them according to a linguistic category, and explaining the causes of the occurring errors. The study shows that a large number of the occurring errors resulted from intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Overgeneralisation is a basic learning technique involving the learner's language, according to (Fauziati & Nugroho, 2019). The overgeneralisation of BE by Indonesians has been recorded by numerous studies (Aziez, 2016;Burhansyah, 2019;Fauziati, 2011Fauziati, , 2017Fauziati & Maftuhin, 2016;Kusumawardani & Adnyani, 2020;Pratiwi et al, 2020;Suwastini et al, 2020). Another findings also revealed the omission of the copula BE (i.e am, is, are).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Overgeneralisation is a basic learning technique involving the learner's language, according to (Fauziati & Nugroho, 2019). The overgeneralisation of BE by Indonesians has been recorded by numerous studies (Aziez, 2016;Burhansyah, 2019;Fauziati, 2011Fauziati, , 2017Fauziati & Maftuhin, 2016;Kusumawardani & Adnyani, 2020;Pratiwi et al, 2020;Suwastini et al, 2020). Another findings also revealed the omission of the copula BE (i.e am, is, are).…”
Section: Discussionmentioning
confidence: 76%
“…Due to the fact that a copula is not required, predication may be expressed using a two-word or one-word nonverbal utterance (Adnyani et al, 2018). Various studies have reported the absence of BE in a student's English production (Burhansyah, 2019;Fauziati, 2011;Fauziati & Maftuhin, 2016;Gayo & Widodo, 2018;Iman, 2020;Kusumawardani & Adnyani, 2020;Mandarani, 2020;P. Sari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Putri, 2023) Idiomatic Expressions: Learners may directly translate idioms or sayings from their first language, resulting in errors or confusion due to the cultural specificity of such expressions. (Burhansyah, 2019) Understanding Cultural Factors for Effective Interventions:…”
Section: Cultural Factors Affecting Errors In Writingmentioning
confidence: 99%
“…Interference, language transfer, and cross-linguistic interference are often called interlinguistic errors. Such errors arise when the learner's rules, systems, or patterns interfere with or prevent them, to some degree, from acquiring second-language rules and patterns (Burhansyah, 2019;Corder, 1981;Yule, 2020). Lado (1964) and Fromkin et al (2018) stated that interference (negative transfer) is the mother tongue (L1) effect on target language performance (L2).…”
Section: Sources Of Errorsmentioning
confidence: 99%